Graph algorithms with neutral atom quantum processors - Dalyac, Constantin; Leclerc, Lucas; Vignoli, Louis; Djellabi, Mehdi; Coelho, Wesley da Silva; Ximenez, Bruno; Dareau, Alexandre; Dreon, Davide; Elfving, Vincent E.; Signoles, Adrien; Henry, Louis-Paul; Henriet, Loïc (The European physical journal. A, Hadrons and nuclei, 2024)
Neutral atom technology has steadily demonstrated significant theoretical and experimental advancements, positioning itself as a front-runner platform for running quantum algorithms. One unique advantage of this technology lies in the ability to reconfigure the geometry of the qubit register, from shot to shot. This unique feature makes possible the native embedding of graph-structured problems at the hardware level, with profound consequences for the resolution of complex optimization and machine learning tasks. By driving qubits, one can generate processed quantum states which retain graph complex properties. These states can then be leveraged to offer direct solutions to problems or as resources in hybrid quantum-classical schemes. In this paper, we review the advancements in quantum algorithms for graph problems running on neutral atom Quantum Processing Units (QPUs), and discuss recently introduced embedding and problem-solving techniques. In addition, we clarify ongoing advancements in hardware, with an emphasis on enhancing the scalability, controllability and computation repetition rate of neutral atom QPUs.